Transitioning to a sustainable circular economy: The transformation required to decouple growth from environmental degradation - Voulvoulis, Nikolaos (Frontiers in Sustainability, 2022)
The UN 2030 agenda of Sustainable Development Goals (SDGs) envisions a future of inclusive equity, justice and prosperity within planetary boundaries, and places an important emphasis on ending poverty (SDG 1) and on sustainable economic growth (SDG 8). Target 8.4 refers to the need to improve global resource efficiency in consumption and production, and decoupling economic growth from environmental degradation, the ultimate goal of a sustainable circular economy. Here, we explore the potential of the transition to such an economy, and discuss the transformation required for moving away from our current model of consumption with its ever increasing generation of waste. The primary aim of such transformation is to rethink what we understand as growth, in order to redefine what is meant by progress and, in the process, redesign our economies, ultimately decoupling our prosperity from material consumption, carbon emissions and waste. Dematerialisation, servitisation, collaborative consumption and a shift from ownership to access have the potential to restructure the economics of consumption, accelerate decoupling, and help us to envision and potentially create a circular economy that delivers social, economic and environmental benefits for all. However, their current deployment without policy steer, public support and appropriate technology developments could turn to be a missed opportunity for ensuring sustainable economic growth fully aligned with sound environmental stewardship and social development, and the transition to a truly sustainable circular economy.